Strategic Partnerships Between Industry and Academia: A Case of Tetra Pak and Lund University Crafting Context-Specific KPIs for Collaborative Success - Uddenäs,Matilda; Avntia,Christina (2025)
Strategic University-Industry Collaborations (UICs) are vital for innovation, yet evaluating their multifaceted outcomes presents a significant challenge. This thesis addresses this gap by investigating performance measurement in UICs through an in-depth case study of the long-standing strategic partnership between Tetra Pak and Lund University. By employing a qualitative methodology, incorporating semi-structured interviews and case-related document analysis, the research found that current evaluation practices within the partnership are mostly informal and lack a comprehensive Key Performance Indicator (KPI) framework. The primary contribution of this thesis is the development of a systematic methodology for constructing a tailored KPI framework to assess UIC outcomes. This was achieved through systematically reviewing and adapting established KPIs from existing literature to the case context; proposing novel and context-specific KPIs derived from empirical findings and the partnership’s strategic objectives; prioritizing these indicators through a ranking system that considers both the strategic relevance and the ease of measurement. The developed framework, while grounded in the specific case, provides insights and a structured approach for other UICs seeking to more effectively evaluate their collaborative success.
Keywords: University-Industry Collaboration (UIC); Strategic Partnerships; Performance Measurement; Key Performance Indicators (KPIs); Outcome Evaluation; Case Study; Innovation